Interaction between Policy Rates and Inflation: A Panel Analysis of the Effects of Monetary Duality on Bank Profitability in Morocco - El Aboudi, Sara; Biaz, Sanae; Aboukinane, Mohamed Amine (International Journal of Economics and Financial Issues, 2025)
This article explores the concept of monetary duality to analyze how the interaction between the policy rate and inflation affects the profitability of commercial banks in Morocco. To accomplish this, we utilized econometric panel data modeling, focusing on a sample of six banks from 2010 to 2023. The results indicate that neither the policy rate nor inflation, when considered individually, significantly impacts bank profitability. However, their interaction becomes significant after correcting the model, suggesting a potential moderating effect of inflation and implying that the effectiveness of interest rates depends on the inflationary context. Additionally, the analysis highlights the varying influence of certain structural variables. Consequently, the study offers targeted recommendations for Bank Al-Maghrib and banking institutions, and it opens avenues for future research into non-linear effects and banking dynamics.